Emergency department crowding and mortality: an observational multicenter study in Sweden - Wretborn, Jens; Wilhelms, Daniel B.; Ekelund, Ulf (Frontiers in Public Health, 2023)
Background Emergency department (ED) crowding is a serious problem worldwide causing decreased quality of care. It is reasonable to assume that the negative effects of crowding are at least partially due to high staff workload, but previous crowding metrics based on high workload have not been generalisable to Swedish EDs and have not been associated with increased mortality, in contrast to, e.g., occupancy rate. We recently derived and validated the modified Skåne Emergency Department Assessment of Patient Load model (mSEAL) that measures crowding based on staff workload in Swedish EDs, but its ability to identify situations with increased mortality is unclear. In this study, we aimed to investigate the association between ED crowding measured by mSEAL model, or occupancy rate, and mortality. Methods All ED patients from 2017-01-01 to 2017-06-30 from two regional healthcare systems (Skåne and Östergötland Counties with a combined population of approximately 1.8 million) in Sweden were included. Exposure was ED- and hour-adjusted mSEAL or occupancy rate. Primary outcome was mortality within 7 days of ED arrival, with one-day and 30-day mortality as secondary outcomes. We used Cox regression hazard ratio (HR) adjusted for age, sex, arrival by ambulance, hospital admission and chief complaint. Results We included a total of 122,893 patients with 168,900 visits to the six participating EDs. Arriving at an hour with a mSEAL score above the 95th percentile for that ED and hour of day was associated with an non-significant HR for death at 7 days of 1.04 (95% CI 0.96–1.13). For one- and 30-day mortality the HR was non-significant at 1.03 (95% CI 0.9–1.18) and 1.03 (95% CI 0.97–1.09). Similarly, occupancy rate above the 95th percentile with a HR of 1.04 (95% CI 0.9–1.19), 1.03 (95%CI 0.95–1.13) and 1.04 (95% CI 0.98–1.11) for one-, 7- and 30-day mortality, respectively. Conclusion In this multicenter study in Sweden, ED crowding measured by mSEAL or occupancy rate was not associated with a significant increase in short-term mortality.